Donne straniere nel libro di Rut e nell’inizio del libro dei Proverbi (capp. 1–9) - Donatella Scaiola (The Biblical Annals)
The texts of Prov 1–9 and Ruth present the reader with contrasting visions concerning the relationship with the ‘other.’ In spite of the still-open extensive debate on the identification of the female figure described in Prov 1–9, it seems fairly certain that both texts can be ascribed to the post-exilic period and thus fall within the issue of mixed marriages, which can be read at various levels: religious, identity, economic, also thanks to the elaboration of an extensive exegesis of the biblical texts.